Studies On Blood Profile Of Healthy And Infected Hanuman Langur (Presbytis Entellus) - Parmar, S.M.; Jani, R.G.; Jacob , Ninan (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted on healthy (n=19) and infected (n=15) hanuman langurs of Gujarat state to establish the normal hematological and biochemical values in the species. In both the sexes of healthy langurs hematological values were noted within the normal range. Hb, TEC, PCV and TLC values in diseased conditions (stomatitis, diarrhoea and respiratory infections) were apparently higher and in disorder conditions (infected wound, electrocution and road accident) they were significantly lower than the values of healthy animals in both the sexes. Blood glucose, BUN, calcium, AST and ALT levels were found to be higher in the healthy female langurs than in the males whereas the levels of total protein, albumin, globulin, creatinine and phosphorus were higher in males than in females. The values of globulin, calcium and AST in the infected animals (infected wound, electrocution and road accident) were found to be lower than those in the healthy animals of both the sexes. The present findings on haemato-biochemical values in healthy langurs would serve as guideline.
Keywords: Biochemical values; Hematological values; Hanuman langur; Healthy; Infected; Gender effect